1986
DOI: 10.3181/00379727-182-42332
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive Effect of  9-Tetrahydrocannabinol in Vitro on Phagocytosis by Murine Macrophages

Abstract: Incubation of normal mouse peritoneal cells consisting of over 90% phagocytizing macrophages with A9-tetrahydrocannabinol (THC) resulted in a inhibition of phagocytic function. The THC in a dose-related manner suppressed the percentage of macrophages per culture which ingested yeast and the average number of yeast particles ingested by the phagocytizing macrophages. The vehicle used to suspend the THC in vitro, i.e., DMSO, had no detectable effect on macrophage function. Suppression of phagocytosis with no eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…Although, there have been reports indicating that the endocannabinoid system is important in regulating DC biology (Table 1), detailed studies addressing the effects of cannabinoids on cellular processes in DC are relatively scarce. In macrophages, however, it was shown that cannabinoids affect phagocytosis, NO- and cytokine production as well as the capacity to process and present soluble peptide antigens [52,53,54,55,56]. Although, not formely proven, it is possible that cannabinoids affect DC functions in similar ways to that reported for macrophages.…”
Section: Cannabinoids and Modulation Of Dendritic Cell Functionmentioning
confidence: 98%
“…Although, there have been reports indicating that the endocannabinoid system is important in regulating DC biology (Table 1), detailed studies addressing the effects of cannabinoids on cellular processes in DC are relatively scarce. In macrophages, however, it was shown that cannabinoids affect phagocytosis, NO- and cytokine production as well as the capacity to process and present soluble peptide antigens [52,53,54,55,56]. Although, not formely proven, it is possible that cannabinoids affect DC functions in similar ways to that reported for macrophages.…”
Section: Cannabinoids and Modulation Of Dendritic Cell Functionmentioning
confidence: 98%
“…(a) by down‐regulating macrophage contact‐dependent cytolysis of tumor cells [92]; and (b) by altering both antigen processing [93] and the expression of select macrophage‐associated proteins [94,95]. Incubation of P388D1 macrophage cells in culture with cannabinoids resulted in a dose‐dependent inhibition of cell propagation, DNA synthesis and phagocytosis [96,97]. In humans, cannabinoids inhibited peripheral blood macrophage spreading and phagocytosis [98].…”
Section: Role Of Endocannabinoids In the Modulation Of Immune Responsesmentioning
confidence: 99%
“…Incubating P388D1 macrophage cell cultures with THC results in a dose-dependent inhibition of cell propagation, DNA synthesis, and phagocytosis (24). In earlier reports, THC was found to inhibit human peripheral blood macrophage spreading and phagocytosis of yeast (25)(26)(27).…”
Section: Figmentioning
confidence: 99%